Coordination and symmetry patterns during the drop vertical jump, 6‐months after first‐time lateral ankle sprain. Issue 10 (25th May 2015) - Doherty, Cailbhe; Bleakley, Chris; Hertel, Jay; Caulfield, Brian; Ryan, John; Sweeney, Kevin; Patterson, Matthew R.; Delahunt, Eamonn
ABSTRACT To evaluate the adaptive movement and motor control patterns of a group with a 6‐month history of first‐time lateral ankle sprain (LAS) injury during a drop vertical jump (DVJ) task. Fifty‐one participants with a 6‐month history of first‐time acute LAS injury and twenty controls performed a DVJ task. 3D kinematic and sagittal plane kinetic profiles were plotted for the lower extremity joints of both limbs for the drop jump (phase 1) and drop landing (phase 2) phases of the DVJ. Inter‐limb symmetry and the rate of impact modulation (RIM) relative to bodyweight (BW) during both phases of the DVJ were also determined. LAS participants displayed bilateral increases in knee flexion and an increase in ankle inversion during phases 1 and 2, respectively. They also displayed reduced ankle plantar flexion on their injured limb during both phases of the DVJ (p < 0.05); increased inter‐limb asymmetry of RIM was noted for both phases of the DVJ, while the moment‐of‐force profile exhibited bilaterally greater hip extensor dominance during phase 1. Participants with a 6‐month history of first‐time LAS display some movement patterns consistent with those observed in chronic ankle instability populations during similar tasks. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1537–1544, 2015.